IL-17 and TNF-α Are Key Mediators of Moraxella catarrhalis Triggered Exacerbation of Allergic Airway Inflammation - Alnahas, Safa; Hagner, Stefanie; Raifer, Hartmann; Kilic, Ayse; Gasteiger, Georg; Mutters, Reinier; Hellhund, Anne; Prinz, Immo; Pinkenburg, Olaf; Visekruna, Alexander; Garn, Holger; Steinhoff, Ulrich (Frontiers in Immunology, 2017)
Alterations of the airway microbiome is often associated with pulmonary diseases. For example, detection of the bacterial pathogen Moraxella catarrhalis in the upper airways is linked with an increased risk to develop or exacerbate asthma. However, the mechanisms by which M. cattarhalis augments allergic airway inflammation (AAI) remains unclear. We here characterized the cellular and soluble mediators of M. catarrhalis triggered excacerbation of AAI in wt and IL-17 deficient as well as in animals treated with TNF-alpha and IL-6 neutralizing antibodies. We compared the type of inflammatory response in M. catarrhalis infected, HDM-allergic and animals infected with M. catarrhalis at different time points of HDM sensitization. We found that airway infection of mice with M. catarrhalis triggers a strong inflammatory response with massive neutrophilic infiltrates, high amounts of IL-6 and TNF-alpha and moderate levels of CD4+ T cell derived IFN-gamma and IL-17. If bacterial infection occured during HDM allergen sensitization, the allergic airway response was exacerbated, particularly by the expansion of Th17 cells and increased TNF-alpha levels. Neutralization of IL-17 or TNF-alpha but not IL-6 resulted in accelerated clearance of M. catarrhalis and effectively prevented infection-induced exacerbation of AAI. Together, our data demonstrate an essential role for TNF-alpha and IL-17 in infection-triggered exacerbation of allergic airway inflammation.